Cold-Formed Steel U-Section Encased in Simple Support Reinforced Concrete Beam. - Kama, Ahmed Youssef; Khalil, Nader Nabih (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Cold-formed steel sections are widely used in construction work as its low cost. This paper presents a series of bending tests, to examine the influence of encasing cold-formed steel (U-section) in a reinforced concrete beam on the beams capacities, mode of failure and ductility. The cold-formed steel section breadth, height, and length are the main parameters studied and presented. Eight full-scale encased composite beams have tested under lateral loading up to failure, in addition, to one full-scale reinforced concrete beam (without cold-formed steel sections). The experimental results have recorded and monitored to clarify the influence of the studied parameters on the composite beam behavior. The experimental results have compared with the reference beam. It has found that the cold-formed steel (U-section) increased the beam load carrying capacity and improved the beam ductility. It has observed that encasing the formed steel sections reduced the influence of the steel sections local buckling